Communication to promote physical activity in family case study in community medicine for under graduate medical students - Kowli, Shobha; Sabale, Rupali (International Journal Of Community Medicine And Public Health, 2016)
Background: In current MBBS curriculum, adequate importance is not given to communication to promote physical activity (PA). However, there is a need to train undergraduates for counseling on PA as it has beneficial effect in prevention of non-communicable diseases. Methods: After an ethical committee approval and written informed consent of the 2nd year MBBS students, a pre-test assessment was done on PA. An interactive educational session on PA and communication skills was conducted and then again post-test assessment was done. During family case study, each student assessed their allotted older adult family member for PA using rapid assessment for physical activity questionnaire and counselled them accordingly. Faculty assessed student’s communication skills using kalamazoo essential element communication checklist-adapted (KEECC-A) and gave immediate constructive feedback. Later feedback of students and faculty were taken to evaluate the designed curriculum for physical activity. Data was entered in the excel sheet and primer-6 was used for analysis. Results: Out of total 50 students, 35 students enrolled in the study. There was statistically significant improvement in the knowledge regarding PA. Almost 58% could effectively counsel for PA. There was overall positive feedback from the students and teachers. 71% students felt PA should be part of the regular curriculum in community medicine. Conclusions: There was significant improvement in knowledge of students regarding PA. Students expressed need to be trained in counselling for PA.